Understanding help-seeking intentions in male military cadets: An application of perceptual mapping. (December 2016) - Bass, Sarah; Muñiz, Javier; Gordon, Thomas; Maurer, Laurie; Patterson, Freda
Abstract Background Research suggests that men are less likely to seek help for depression, substance abuse, and stressful life events due to negative perceptions of asking for and receiving help. This may be exacerbated in male military cadets who exhibit higher levels of gender role conflict because of military culture. Methods This exploratory study examined the perceptions of 78 male military cadets toward help-seeking behaviors. Cadets completed the 31-item Barriers to Help Seeking Scale (BHSS) and a component factor analysis was used to generate five composite variables and compare to validated factors. Perceptual mapping and vector modeling, which produce 3-dimensional models of a group's perceptions, were then used to model how they conceptualize help-seeking. Results Factor analysis showed slightly different groupings than the BHSS, perhaps attributed to different characteristics of respondents, who are situated in a military school compared to general university males. Perceptual maps show that cadets perceive trust of doctors closest to them and help-seeking farthest, supporting the concept that these males have rigid beliefs about having control and its relationship to health seeking. Differences were seen when comparing maps of White and non-White cadets. White cadets positioned themselves far away from all variables, while non-White cadets were closest to "emotional control". Conclusion To move these cadets toward help-seeking, vector modeling suggests that interventions should focus on their general trust of doctors, accepting lack of control, and decreasing feelings of weakness when asking for help. For non-White cadets a focus on self-reliance may also need to be emphasized. Use of these unique methods resulted in articulation of specific barriers that if addressed early, may have lasting effects on help-seeking behavior as these young men become adults. Future studies are needed to develop and test specific interventions to promote help-seeking among military cadets.